Influence of Synthetic Parameters and Reaction Conditions on Properties of CexZr1-xO2 for CO Preferential Oxidation Reaction in H2-rich Gases. (2015) - Deng, Lian; He, Sufang; Huang, Si; Wang, Jing; He, Dedong; He, Suyun; Luo, Yongming
Abstract: Cex Zr1-x O2 (x=0-1) catalysts were prepared by urea grind combustion method (UGC) and tested for CO preferential oxidation in H2 -rich gases. The catalytic performances of Cex Zr1-x O2 -UGC-400 are comparable to Cex Zr1-x O2 -SG-400 and higher than Cex Zr1-x O2 -SA-400. The optimal Ce/Zr molar ratio, calcination temperature and urea addition (R value) for synthesizing Cex Zr1-x O2 catalysts are Ce/Zr = 4:1, 300 o C and R = 1.0, respectively. Ce0.8 Zr0.2 O2 catalyst prepared with this route can well adapt the change of gas hourly space velocity (GHSV), and no any obvious change is observed both in CO conversion and O2 selectivity with GHSV increasing from 12000 to 48000 h -1 . Both CO conversion and O2 selectivity of Ce0.8 Zr0.2 O2 maintains relative stability during 72 h time-on-stream test.